Ответы и объяснения

2012-04-26T08:32:28+00:00

3,2х-10,24+5,5х-12,1=8,7х-22,34

х=3,2  8,7*3,2-22,34=5,5

 

6,3х+15,12-9,1х-12,74=-2,8х+2,38

х= -1,4   -2,8*(-1,4)+2,38=6,3

Лучший Ответ!
2012-04-26T08:37:01+00:00

1)

3,2(х-3,2)+5,5(х-2,2)

3,2х-3,2*3,2+5,5х-5,5*2,2=8,7 х-3,2*3,2-5,5*2,2

 

подставяем х

8,7*3,2-3,2*3,2-12,1=3,2(8,7-3,2) -5,5*2,2=3,2*5,5-5,5*2,2=5,5(3,2-2,2)=5,5

2)

6,3(х+2,4)-9,1(х+1,4) при х= -1,4

 

6,3х-9,1х+6,3*2,4-9,1*1,4=-2,8х+6,3*2,4-9,1*1,4 подставляем значение х

-2,8*(-1,4)+6,3*2,4-9,1*1,4=1,4(2,8-9,1)+6,3*2,4=1,4*(-6,3)+6,3*2,4=6,3(2,4-1,4)=6,3